“Get out of my country!”: confronting racism and xenophobia through inclusive mathematics education - Carrijo, Manuella Heloisa de Souza (2023)
This research aims to discuss possibilities for inclusive mathematics education that combine the reality of immigrant students with reference to structural racism. Thus, it seeks to inquire about and analyse a social situation, understand the changes needed, and consider possibilities in mathematics education for engaging in social transformation toward overcoming many kinds of social borders and exploitation structures. The central question is: what can inclusive mathematics education do in the context of international immigration shaped by social and racial structured injustices? In this sense, the aim is to highlight the importance of mathematics education addressing issues such as racism, citizenship, globalisation, ghettoisation, and so on, and discuss how to expand the inclusive and anti-racism mathematics education field to go deeper in considering immigration issues, as well as outlining practical possibilities for mathematics classes, taking inspiration from already completed investigations, as well as imagined hypothetical situations. Using a qualitative approach, data was produced with fourteen participants who live in the state of São Paulo - in the context of the Covid 19 pandemic. The research participants were mathematics teachers from public schools, and immigrants from Venezuela and Haiti. The initial criterion for choosing the research participants was their willingness and ability to participate in the research remotely and engage in Portuguese conversation. Data was produced through interviews, which were recorded in audio and video. The data opened windows to studying the social scenarios in which the participants live, through which an in-depth theoretical discussion was possible. The accounts of the lived experiences of immigrants and mathematics teachers constituted elements of the social and educational framework. Such elements were crucial for discussions about possibilities for mathematics education. The results of this study show a context permeated by several mechanisms of exclusion and discrimination, reflecting the context of the mathematics classroom. These results point towards the need to rethink inclusive mathematics education in terms of immigrant students and anti-racism actions, so that it can be a powerful environment for students to get to know each other and the world, increasing their awareness of their place in the world and broadening from a local to a global perception. Five types of microexclusion were identified against immigrant students; they are exoticisation, misleading identification, assimilation, second-class citizens, and misprising. Stigmatisation and exclusion practices are presented in a gradient of subtlety and dissimulation, conducive to reinvigorating racism and xenophobia. Other research results are the projects: The Beauty of Diversity, Global Mobility, and Ghettoisation—Is Racism a Factor?. Such projects result from pedagogical imagination-stimulated creativity and offer an opening to thinking about the possibilities of overcoming borders in mathematics classes; they involve imagining the school, the classes, and the students.